The Effect of Food Price Changes on Child Labor: Evidence from Uganda - Raymond B. Frempong; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2017)
A majority of people in developing countries spend about 60 percent of their income on food, even though most of them are farmers. Hence, a change in food prices affects both their revenue as well as expenditure, and thereby their labor market decisions. Using the Uganda National Panel Survey and monthly regional food prices, this paper examines the effect of exogenous changes in food prices on child labor. The econometric evidence shows that an increase in food prices leads to an increase in the probability and intensity of child labor. We find the effect of food price increases to be smaller among landowning households, which is consistent with the view that landowning households can better compensate for price shocks. The results suggest that periodic shocks in food prices may have longer lasting effects on human capital development and poverty in developing countries.
Keywords: O12; Q18; J20; 330; Development; Child labor; Exogenous shock; Food prices